Establishment of a Cell Necroptosis Index to Predict Prognosis and Drug Sensitivity for Patients With Triple-Negative Breast Cancer - Xie, Jindong; Tian, Wenwen; Tang, Yuhui; Zou, Yutian; Zheng, Shaoquan; Wu, Linyu; Zeng, Yan; Wu, Song; Xie, Xinhua; Xie, Xiaoming (Frontiers in Molecular Biosciences, 2022)
Background: Necroptosis has been an alternatively identified mechanism of programmed cancer cell death, which plays a significant role in cancer. However, researches about necroptosis-related long non-coding RNAs (lncRNAs) in cancer are still few. Moreover, the potentially prognostic value of necroptosis-related lncRNAs and their correlation with immune microenvironment remains unclear. The present study aimed to explore the potential prognostic value of necroptosis-related lncRNAs and their relationship to immune microenvironment in triple-negative breast cancer (TNBC). Methods: RNA expression matrix of patients with TNBC was obtained from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases. 107 patients of GSE58812, 159 patients of TCGA, and 143 patients of GSE96058 were included. Necroptosis-related lncRNAs were screened by Cox regression and Pearson correlation analysis with necroptosis-related genes. By Lasso regression analysis, 9 necroptosis-related lncRNAs was employed and a cell necroptosis index (CNI) was established, and then we evaluated its prognostic value, clinical significance, pathways, immune infiltration, and chemotherapeutics efficacy. Results: Based on the CNI value, TNBC patients were divided into high- and low-CNI groups, and patients with high CNI had worse prognosis, more lymph node metastasis and larger tumor (p < 0.05). The receiver operating characteristic (ROC) analysis showed that the signature performed well. The result of infiltration proportion of different immune cells infiltration further explained that TNBC patients with high CNI had low immunogenicity, leading to poor therapeutic outcomes. Moreover, we found significant differences of the IC50-values of various chemotherapeutic drugs in two CNI groups, which might provide a reference to make a personalized chemotherapy for them. Conclusion: The novel prognostic marker-CNI, which could not only precisely predict the survival probability of patients with TNBC, but also demonstrate a potential role in anti-tumor immunity and drug sensitivity.